2014
DOI: 10.1097/aco.0000000000000047
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response to trauma

Abstract: Purpose of this review Recent studies have changed our understanding of the timing and interactions of the inflammatory processes and coagulation cascade following severe trauma. This review highlights this information and correlates its impact on the current clinical approach for fluid resuscitation and treatment of coagulopathy for trauma patients. Recent findings Severe trauma is associated with a failure of multiple biologic emergency response systems that includes imbalanced inflammatory response, acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 78 publications
0
25
0
Order By: Relevance
“…The disturbance, traction and the compression of the thoracic cavity by pneumoperitoneum during surgery are the important elements of trauma 28 . Studies have demonstrated that trauma is closely associated with the stability of the internal environment 29 , 30 . Obese patients suffer from many underlying diseases and exhibit reduced cardiopulmonary function and operational tolerance; thus, their internal environment is relatively sensitive to trauma 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The disturbance, traction and the compression of the thoracic cavity by pneumoperitoneum during surgery are the important elements of trauma 28 . Studies have demonstrated that trauma is closely associated with the stability of the internal environment 29 , 30 . Obese patients suffer from many underlying diseases and exhibit reduced cardiopulmonary function and operational tolerance; thus, their internal environment is relatively sensitive to trauma 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Disease states associated with inflammation like trauma, burns, sepsis, and acute pancreatitis are characterized by a marked reduction in the vascular endothelial glycocalyx [ 45 ]-[ 47 ]. The glycocalyx is the primary structure limiting free fluid flux across the vascular space [ 35 ].…”
Section: Reviewmentioning
confidence: 99%
“…The endothelial glycocalyx plays an important role in vascular barrier regulation [4] , WBC adhesion [43] , coagulation [44; 45] , angiogenesis [46] , and tissue repair [47] . Nearly all of these functions are relevant to perioperative clinicians.…”
Section: Discussionmentioning
confidence: 99%